Comparative effects of dietary sodium butyrate and tributyrin on broiler chickens’ performance, gene expression, intestinal histomorphometry, blood indices, and litter - Elshaimaa Ismael; Shaimaa Kamel; Ebtihal M. M. Elleithy; Manal R. Bekeer; Khaled Nasr El-din Fahmy (Scientific Reports)
Abstract Sodium butyrate and tributyrin are known to enhance broiler chicken performance. In this study, 1,000 Arbor Acres broiler chicks were assigned to four dietary treatments (250 birds each; six replicates of 40–42 birds): a control basal diet (CON), or the same diet supplemented with either 500 g/ton tributyrin (40%) + copper + essential oils (TB-500), 300 g/ton di- and tri-butyrin (60%) (TB-300), or 500 g/ton coated sodium butyrate (40%) (SB-500). Weekly growth parameters were recorded, and on Day 35, carcass traits, serum biochemistry, immunity, gene expression (mTOR, TLR4, NBN), intestinal morphology, caecal microbiota, and litter hygiene were assessed. TB-300 improved body weight (+ 4.6%, P = 0.014), FCR (− 5.2%, P = 0.032), and European Production Efficiency Factor (EPEF) (+ 14.9%, P = 0.006). SB-500 significantly reduced litter Clostridia (P < 0.0001) and aerobic bacteria (P = 0.026) counts, while all butyrate treatments lowered caecal aerobic bacterial levels (P = 0.041). TB-300 and SB-500 enhanced duodenal villi height (P < 0.0001) and crypt-villus ratio (P < 0.001); TB-500 had the deepest duodenal crypts (P = 0.003). Jejunal and ileal morphology improved with most of the supplements, particularly TB-500 (P < 0.0001; P = 0.050). All butyrate treatments increased serum total proteins (P = 0.015) and digestive enzymes (lipase, P < 0.0001; protease, P = 0.001). TB-300 and SB-500 significantly lowered serum lipids (P = 0.024), urea (P = 0.018), and aspartate aminotransferase (AST) (P = 0.027), while enhancing mTOR and NBN gene expression (P < 0.0001). TLR4 expression was upregulated in all butyrate-treated groups (P < 0.0001). Each form of butyrate supplementation exerts distinct beneficial effects on growth, gut health, and physiological performance in broiler chickens.